The Effect Of The Teaching Factory And Work-Life Balance On The Performance Of Teachers At Baso State Vocational School 1 - Yulihar Nova; Rina Supryanita, Fitria Fitria, Dian Rahmawaty, Nurfitriyenny Nurfitriyenny (STIE AMKOP, 2026)
Variations in teacher attendance rates between 2022 and 2025 demonstrate the uneven performance of instructors at SMK Negeri 1 Baso. Performance may have been impacted by the difficulty of putting the teaching factory program into practice. The purpose of this study is to partially and simultaneously examine how the teaching factory and work-life balance affect teachers' performance at SMK Negeri 1 Baso. Fifty-two teachers participated in a quantitative survey. A 1–5 Likert scale questionnaire was used for data collection. SEM-PLS with SmartPLS 3 was used for data analysis. Teacher performance was significantly improved by the teaching factory (β = 0.512, t = 3.348, p < 0.001). There was no significant impact from work-life balance (β = 0.314, t = 1.785, p = 0.037). When combined, the two factors accounted for 61.2% of the variation in teacher performance (R2 = 0.612, F = 38.64, p < 0.001). The most important factor was the teaching factory (f2 = 0.285). The secret to raising teacher performance is to strengthen the teaching factory's implementation. The workload has not yet been adequately balanced by work-life balance. It is recommended that schools give the teaching factory program top priority. Keywords: Role; Teaching Factory; Work-life balance; Teacher performance; Vocational High School